Maldanidae (Polychaeta) from west Greenland waters. - Wesenberg-Lund, Elise (Meddelelser om Grønland, 1948)
[From Introduction:] During my studies on arctic Polychaeta especially intended for publication in the Report of the Danish "Ingolf" Expedition I found in the various collections in the Zoological Museum a fairly great number of Maldanids from more or less shallow waters west of Greenland, an area which is beyond the scope of the "Ingolf" report. The material appeared to be fairly well preserved although many of the specimens were fragmentary, but in most cases I succeeded in ascertaining the mutual interdependence of the anterior and posterior parts. A study of the literature showed that by far the greater part of the species hitherto known from West-Greenland waters was represented in the collections, which besides also comprises four new species and seven species new to this area. I therefore consider it adequate to publish a separate paper on West-Greenland Maldanids, most probably comprising all the species from these waters. For the sake of completeness, however, the specimens from abyssal regions are also concluded in this revision, although they ought to be published in the "Ingolf" report, and therefore the description of these abyssal species will be rather compendious and only references to the present description with the accompanying figures will be given in the "Ingolf" report.—Nearly every species mentioned is accompanied by drawings of the cephalic lobe, the pygidium and the various kinds of setae, as far as they offer anything of interest, and I wish to bring the scientific drawer Mr. Poul H. Winther my best thanks for his fine drawings and excellent collaboration. I also owe my sincerest thanks to the Carlsberg Foundation for finantial support for the performance of the drawings.
AnnelidaBase